Dampak Rasisme Terhadap Keturunan Afrika-Amerika di Politik Pemerintahan Amerika Serikat pada Tahun 2016-2020 - Gilbert Ferdinand Simboh; Halifa Haqqi; Satria Rizaldi Alchatib (Program Studi Hubungan Internasional FISIP Universitas Jayabaya, 2023)
Racism in United States causes tragedy that impact especially in political society in international relations. Donald Trump as US President been a racist to some African-American US political actor, include congress, senate, and also how he picked his executive. Trump makes his political society look racist itself because his visions, insists of Nationalism ; Nativism ; and Protectionism. Those visions gain a lot of pro and contra for uprising white supremacy in way to lead the US country. Begin from racist to his executive that only took one political actor for his cabinet and racist to an African-American senate named Ayanna Pressley. But, on the other side, when people in America make their choice for senate and house in US House of Representatives, they did not make hard time for African-American candidate for advancing to take their place to House of Representatives. There are speculations of how big the impact of Donald Trump racism to US political society. Even though it been a lot of discussed, racist still been an issue in US, especially in political society. To analyze and answer the issue for the problem, the author uses social constructivism and color-blindness to measure how impactful the racism is for the African-American US political actor. In applying the result of this research, the author uses a descriptive text of research. For the data collection methods of the research, the author uses discourse analysis and qualitative data analysis methods.